Analisis Faktor Yang Berhubungan Dengan Aktivitas Sosial Lansia Di Masyarakat - Wahyuni, Endang Sri; Arifiati, Retna Febri (Yayasan Jompa Research and Development, 2025)
Improving social relationships in the elderly. However, the level of elderly participation in social activities is influenced by demographic characteristics such as age, gender, education level, and economic status. This study aims to analyze the relationship between demographic factors and social activities of the elderly.Research Methods: This study uses a quantitative method with a cross-sectional design. Data were collected through questionnaires distributed to 41 elderly people. The research instrument was the Social Activity Scale (SAS). Data analysis was performed using crosstabulation analysis to identify the relationship between demographic variables and social activity.Research Results: The results showed that the majority of respondents had social activity at the